An assessment of factors influencing parents’ decision making when choosing a private school for their children: a case study of Selangor, Malaysia: for sustainable human capital - Yaacob, Noor Alyani; Mohamed Osman, Mariana; Bachok, Syahriah (Elsevier, 2015)
Current perspectives highlight the importance of educational sector in designing the socio-economic development of a country. It accelerates the economic growth through knowledge and skills development by improving the human capabilities, in terms of ensuring that the individuals are confident, perspective and physically active. It is customary to the parents to ensure the best possible educational environment for their children. During the last few decades, private schools in Malaysia have emerged as an essential source of imparting education at various levels. These schools received financing in part or as a whole from tuition fees, fundraising, and alumni contribution. Apart from that, the private sector education has become an important sector for stakeholders to invest. The research emphasized in the analyzing the parents’ motivation in deciding on private school. This paper aims at investigating the factors influencing the parents when selecting a private school as the educational institution for their children. The research analyzed what motivated the parents to make the decision in terms of exploring the strength and weaknesses of these private schools over public schools. The state of Selangor is selected to represent the overall states in Malaysia due to the presence of many qualities and establish private institutions. More than 600 questionnaire forms have been distributed, but to date the response could be ascertained at 510 forms only. Based on the study Social Background/Status, Income Level, School Syllabus, School Environment/Facilities, School Performances, Location, Teacher Quality and Distance were analyzed on their potential relationship. It was found that the parents make the decision based on their income level, social background, followed by the distance and location of the private school when selecting to enroll their children in private schools. The quality of the teacher was placed fifth with sixth factor is the school performance. School environment nominated on seventh and last but not least, the school syllabus was considered in preference.